ANALYSIS OF WORK ENVIRONMENT AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE OF INDUSTRY AND TRADE DEPARTMENT OF PASURUAN DISTRICT: ANALISIS LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DINAS PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN PASURUAN - Aris Mindarwanto; Sutikto; Kurniawan Adi Prayitno; Nanang Kosim; Fariz (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
The purpose of this study was to examine the influence of the work environment and job satisfaction on the performance of employees in the Department of Industry and Trade of Pasuruan Regency. The analysis tools used to describe the work environment and job satisfaction in relation to performance utilized SPSS. Additionally, multiple regression analysis was employed to analyze the influence of motivation and work discipline on the performance of educational staff. The results of the partial hypothesis testing (t-test) for both independent variables, the work environment, and job satisfaction, showed a significant partial influence on the dependent variable, the performance of employees in the Department of Industry and Trade of Pasuruan Regency. Based on the data analysis and discussion, it can be concluded that the research on the work environment and job satisfaction's impact on the performance of employees in the Department of Industry and Trade of Pasuruan Regency has shown that the simultaneous (F-test) testing of the independent variables, the work environment, and job satisfaction, has a significant combined influence on the dependent variable, the employee's performance. Furthermore, the research results revealed that the regression coefficient value for job satisfaction was higher compared to the coefficient value for the work environment. This finding indicates that job satisfaction is the dominant factor influencing employee performance in the Department of Industry and Trade of Pasuruan Regency.